STRATEGI PEMBELAJARAN BERBASIS KECERDASAN JAMAK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DAN BUDI PEKERTI DI SMP NEGERI 3 SENGKANG KABUPATEN WAJO - Gamal, Multasam (Universitas Islam Negeri Alauddin Makassar, 2018)
Multiple intelligence based learning strategies, namely preparation of learning by compiling lesson plans. The implementation of learning consists of preliminary activities (apperception and motivation) consisting of activities of the alpha zone, warmer, pre-teach and scene settings. The core activity is the activities of students facilitated to learn through nine types of intelligence namely linguistic / language intelligence, mathematical-logical, visual-spatial, kinesthetic, musical, interpersonal, intrapersonal, naturalistic, and existential / spiritual. Learning assessment is done authentically using 3 domains, namely cognitive, affective, and psychomotor. Application Results Multiple-based learning strategies can shape the creativity of students who are developed through personal aspects, namely appreciation to students in the form of reinforcement. The driver is inviting students to respect the results of opinions. The process is to invite students to think and conclude again the results of problem solving using their imagination and the product is the work in the form of wall displays.